EVALUASI PROGRAM ORGANISASI PENGGERAK DI SMP NEGERI 1 SUNGAI KAKAP KABUPATEN KUBU RAYA - Sosialisman, Sosialisman (Jurnal Visi Ilmu Pendidikan, 2025)
This research aims to describe the components of Needs Assessment, Program Planning, Formative Evaluation, and Summative Evaluation in the Organizational Activator Program (POP) at State Junior High School 1 Sungai Kakap, Kubu Raya Regency.The research is conducted using a qualitative descriptive approach. The data collection method uses observation techniques, interviews, and documents. The data analysis consists of data collection, data reduction, data presentation, and verification/drawing conclusions. Test the validity of the data using triangulation and member checking.  The main findings of this research are (1) Needs Assessment. Before participating in the Organizer Program (POP), schools faced several challenges in supporting/implementing literacy programs. (2) Program Planning. Program planning is carried out by considering the needs for facilities and infrastructure, resources, and training that have been identified in the needs assessment stage. (3) Formative Evaluation. The school encourages active participation from all stakeholders in the POP program, promoting the importance of involvement in planning and implementation. (4) Summative Evaluation. The Organizer Movement Program at SMP Negeri 1 Sungai Kakap has a significant positive impact on students' learning outcomes, reading interest, writing skills, and critical thinking abilities, as well as enhancing teachers' professionalism in teaching and writing.